Postmodernism in the literature of the Israeli novelist Orly Kastel-Bloom - فكري جواد عبد ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
Postmodernism is a new philosophical stream as an extension that encompasses the fields of literature, art, engineering, and many other episodes of knowledge. It was a product of the Second World War that started with its end. Postmodernism entered and dominated international literature, and wrote many literary works according to the characteristics of postmodernism that were characterized by the use of easy language close to the daily language, the introduction of many quotes into the dialogues of personalities, the multiplicity of heroes and the lack of one hero.            This research is based on the study and analysis of the literary works of the Israeli novelist Orly Kastel-Bloom, which was written in a postmodern style, and examines the role of this writer in the development and crystallization of the postmodern stream in Hebrew literature at the end of the last century and the beginning of the current century.